2004
DOI: 10.1111/j.1365-2559.2004.01729.x
|View full text |Cite
|
Sign up to set email alerts
|

Extensive vascular invasion is a marker of risk of relapse in encapsulated non‐Hürthle cell follicular carcinoma of the thyroid gland: a clinicopathological study of 18 consecutive cases from a single institution with a 11‐year median follow‐up

Abstract: EFC is a low-risk carcinoma, with no patients' deaths after a median follow-up of 11 years. Extensive vascular invasion should be considered as a risk factor for relapse. A conservative surgical approach is recommended. Since relapses may occur up to 14 years after the initial surgery, life-long follow-up is advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
59
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 12 publications
4
59
0
3
Order By: Relevance
“…In the current series, vascular invasion was by far the most pow- erful predictor of recurrence (P Ͻ.0001) in patients with EHC, whereas capsular invasion was not significantly associated with tumor recurrence. This correlation between extent of vascular invasion and adverse outcome was found in a small series of encapsulated non-Hurthle cell follicular carcinomas 5 and in larger series analyzing follicular carcinomas in general without emphasis on its oncocytic variant. 4,20 It is truly remarkable that the number of foci of vascular invasion that place patients at high risk of disease recurrence (Ն 4 vessels) is very close to the number found by Lang et al 4 in 1986 (Ն 5 foci).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…In the current series, vascular invasion was by far the most pow- erful predictor of recurrence (P Ͻ.0001) in patients with EHC, whereas capsular invasion was not significantly associated with tumor recurrence. This correlation between extent of vascular invasion and adverse outcome was found in a small series of encapsulated non-Hurthle cell follicular carcinomas 5 and in larger series analyzing follicular carcinomas in general without emphasis on its oncocytic variant. 4,20 It is truly remarkable that the number of foci of vascular invasion that place patients at high risk of disease recurrence (Ն 4 vessels) is very close to the number found by Lang et al 4 in 1986 (Ն 5 foci).…”
Section: Discussionmentioning
confidence: 69%
“…In 1986, Lang et al 4 studied a large number of follicular carcinomas and demonstrated that the number of foci of vascular invasion is an adverse prognostic sign even in encapsulated tumor. Recently, Collini et al 5 found identical results in encapsulated nononcocytic follicular carcinoma. However, in most publications, including the above-mentioned studies, encapsulated Hurthle cell carcinomas (EHCs) are either not included or diluted with their non-Hurthle cell counterparts and not analyzed separately.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Minor vascular invasion (small number of foci confined to intracapsular vessels) appears to have a low risk of SIR (less than 5%) (28)(29)(30). On the contrary, more than 4 foci of vascular invasion are associated with a poor prognosis, mainly in follicular carcinomas (30)(31)(32). This situation seems to be uncommon in papillary carcinomas, even more in micro PTC, with a prevalence of less than 4% (25,26,28,(33)(34)(35).…”
Section: Resultsmentioning
confidence: 94%